2016
DOI: 10.4314/ahs.v16i1.30
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of diffusion weighted MRI and ADC in differential diagnosis of cavernous hemangioma of the liver

Abstract: Aims: To investigate the use of diffusion weighted magnetic resonance imaging (DWI) and the apparent diffusion coefficient (ADC) values in the diagnosis of hemangioma. Materials and methods:The study population consisted of 72 patients with liver masses larger than 1 cm (72 focal lesions). DWI examination with a b value of 600 s/mm 2 was carried out for all patients. After DWI examination, an ADC map was created and ADC values were measured for 72 liver masses and normal liver tissue (control group). The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…Studies in different types of cancer have also proposed DW-MRI as a marker to distinguish benign and malignant tumors and to evaluate the aggressiveness of cancer based on ADC-values, but that goes beyond the scope of the present study [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in different types of cancer have also proposed DW-MRI as a marker to distinguish benign and malignant tumors and to evaluate the aggressiveness of cancer based on ADC-values, but that goes beyond the scope of the present study [36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies in the past which reported DWI and ADC values to be useful in distinguishing benign vs malignant liver lesion included simple cysts [ 6 , 8 , 10 , 16 ]. In daily practice, simple liver cysts are easily identified as they demonstrate distinct fluid MRI signal characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…There has been promising evidence that ADC may be a viable tool to help discriminate benign versus malignant character of a hepatic lesion [ 1 , 6 , [8] , [9] , [10] , [11] , [12] , [13] ]. However, there have been conflicting reports in literature regarding the usefulness of DWI in this regard.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical settings, contrast enhancement has been widely used in preoperative qualitative diagnosis of focal lesions in the liver, especially in cases of suspected primary hepatocellular carcinoma. For patients with renal failure and contrast agent contraindications, DWI technology provides a kind of noninvasive examination method that is more conducive to impact on the clinical management [41]. The DKI model, an emerging MRI technology, is more sensitive to tissue microstructural complexity and heterogeneity in high b values.…”
Section: Discussionmentioning
confidence: 99%